The structure and reproduction of the algae. Volume II - Foreword, Phaeophyceae, Rhodophyceae, Myxophyceae - Fritsch, F.E. (Cambridge Cambridge University Press, 1959)
Contents: v.2.- foreword, Phaeophyceae , Rhodophyceae, Myxophyceae
Keywords: Algae